IMPACT OF WORKLOAD AND RESPONSIBILITY LOAD ON WORK STRESS AND JOB PERFORMANCE ON CONSTRUCTION PROJECTS DURING THE PANDEMIC - Prasetyaningtyas, Sekar Wulan; Darmawan, Afif; Puhirta, Bevi Prapasatya; Kusmanto, Doni Ardono (Universitas Brawijaya, Indonesia, 2022)
Construction is one of the sectors that the government relies on to contribute to national growth; the impact of this policy is that the number on the projects is not balanced with construction experts, thereby increasing the workload of construction employees, coupled with the pandemic, limiting construction project activities which are labour-intensive activities that require a lot of interaction and physical activity in the field. This study aims to determine the impact of a workload and responsibility load on work stress and job performance in construction projects during the pandemic. This research uses a correlational descriptive quantitative approach: the population in this study is 100 construction employees in Indonesia. The sampling technique is total sampling with multiple linear regression. The result showed that workload significantly affects the responsibility load on construction project workers in Indonesia. The workload has a positive and significant impact on Indonesian construction project workers. Responsibility load has a positive and significant effect on Workstress on Project Construction workers in Indonesia. The influence of responsibility load on work stress is negative and significant. Work stress on employees does not affect job performance on employees. Namely, there is no effect if construction employees have high work stress on their work. It does not affect job performance. The work stress variable has no positive or significant effect on job performance. Further research can incorporate variables that influence job performance, such as workload, responsibility load, work stress, and others, to improve job performance at construction.